Calcitonin receptor‐like (CALCRL) is a marker of stemness and an independent predictor of outcome in pediatric AML - Angenendt, Linus; Wöste, Marius; Mikesch, Jan-Henrik; Arteaga, Maria Francisca; Angenendt, Adrian; Sandmann, Sarah; Berdel, Wolfgang E.; Lenz, Georg; Dugas, Martin; Meshinchi, Soheil; Schliemann, Christoph; Rössig, Claudia (Blood advances, 2021)
We have recently identified the G protein-coupled neuropeptide receptor calcitonin receptor‐like (CALCRL) as an independent prognostic biomarker and a therapeutic target in more than 1500 adult patients with acute myeloid leukemia (AML). Here, we confirmed CALCRL expression as a prognostic factor in a cohort of 284 pediatric patients with AML. High CALCRL expression was independently associated with event-free survival (hazard ratio [HR], 1.87; 95% confidence interval [CI], 1.36-2.57; P = .0001), overall survival (HR, 1.55; 95% CI, 1.06-2.27; P = .025), and cumulative incidence of relapse (HR, 2.10; 95% CI, 1.49-1.96; P < .0001) when adjusting for age, white blood cell count, and genetic risk. Despite its association with leukemia stem cell signatures, CALCRL expression remained associated with all end points when compared with the 17-gene leukemic stem cell score. The strong association of CALCRL expression with the risk of relapse also in the pediatric population supports its role as novel age-independent master regulator of relapse-initiating, drug-tolerant AML cells in humans.